"The lab isn't life": Black engineering graduate students reprioritize values at the intersection of two pandemics. Issue 2 (2nd April 2023) - Coley, Brooke; Thomas, Katreena
Abstract: Background: Black engineering graduate students represent a critical and understudied population in engineering education. Gaining an understanding of the lived experiences of Black engineering graduate students while they are simultaneously weathering two pandemics, COVID‐19 and systemic racism, is of paramount importance. Purpose/Hypothesis: Black engineering graduate students hold a unique duality, as both Black people in the United States and Black graduate students in US engineering programs that espouse white supremacist ideals. Their real‐world experiences necessitate understanding, and this paper highlights the related impact on the students themselves, their adaptations to the pandemics, and how those adaptations relate to and affect their support needs and navigation of their engineering academic environments. Design/Method: An interpretive phenomenological analysis (IPA) approach was combined with community‐based participatory action research and was situated in Boykin's Triple Quandary. A family check‐in was conducted with 10 Black engineering graduate students enrolled in doctoral programs across the country to delve deep into their lived experience as a cultural community. Results: Findings include an emergent framework of Black engineering graduate student values in response to the pandemics. These values aligned with the Black Cultural Ethos, demonstrating an adoption of collectivistic cultural values in times of crises. Further, COVID‐19 and systemic racism differentially impacted Black engineering graduate students and, thus, the manifestations of their values. Conclusion: For institutions to be able to effectively support their Black engineering graduate students, they must gain awareness of the students' experiences, values, and needs, in general, and amid crises specifically. The findings presented here provide a critical window into this information.